Management of Respiratory Viral Infection in Children - Serban, Mariana; Costin, Silvia Aura; Verga, Gabriela Isabela; Capat, Adriana; Ambrose, Lenuta; Draganescu, Miruna Luminita (Technium BioChemMed, 2024)
Respiratory viral infections are a major cause of morbidity and mortality in children, posing a significant burden on healthcare systems. A proper understanding of the epidemiology, diagnostic methods, and management strategies is essential to improve paediatric care and avoid the unjustified use of antibiotics, thereby contributing to the fight against antimicrobial resistance. Aim: This study aims to provide a comprehensive synthesis of the literature on respiratory viral infections in children, focusing on the role of antibiotics and the importance of preventive measures. Methodology: For this literature review, an initial 87,000 articles were identified from seven databases, following the PRISMA protocol. After removing duplicates and applying exclusion criteria, 200 articles were reviewed, of which 43 were selected for the final synthesis. Results: The study highlights the diversity of viral agents involved, including RSV, influenza viruses, and rhinoviruses. It emphasizes that antibiotics are effective only in cases of bacterial superinfections. Vaccination and hygiene measures are crucial for prevention, while health education plays a central role in reducing infection incidence. Conclusions: Optimal management of respiratory viral infections in children requires a multidisciplinary approach centred on prevention and accurate diagnosis. The study underscores the need for evidence-based protocols, as well as the importance of education and hygiene measures in paediatric communities. These findings provide a solid foundation for developing tailored health policies and contribute to improving clinical practices in paediatrics.